PENGARUH PENDEKATAN DEEP LEARNING TERHADAP PENGUATAN KARAKTER PROFIL PELAJAR PANCASILA PADA SISWA KELAS V SEKOLAH DASAR NEGERI MRANGGEN 02 POLOKARTO - Putri Mawarsari, Putri Mawarsari; I Made Ratih Rosanawati; Suwarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Independent Curriculum demands a learning transformation from rote memory based surface learning to deep learning that builds both conceptual understanding and student character. This study analyzes the effect of the deep learning approach implemented through the pillars of mindful learning, meaningful learning, and joyful learning on strengthening the Pancasila Student Profile of fifth grade students at SDN Mranggen 02 Polokarto in mathematics learning specifically on bar charts. The research used a quantitative approach with a Pre-Experimental One-Group Pretest-Posttest Design on 15 fifth grade students determined through a total sampling technique. The instrument was a 28 item Likert questionnaire that had been tested for validity and reliability. Data were analyzed using the Shapiro Wilk normality test, the Paired Sample t-Test, and the N-Gain Score test. The results show the data are normally distributed (p > 0.05) and there is a significant difference between the pretest and posttest scores (p < 0.05) with an improvement in the moderate to high categories. These findings indicate that the deep learning approach has the potential to meaningfully strengthen the character of elementary school students.